Rice Planting Machine Design with Uniform Spacing Mechanism: Desain Mesin Penanam Padi dengan Mekanisme Jarak Tanam yang Seragam - Aftian, Muhammad Alriz Nur; Mulyadi (Indonesian Journal of Innovation Studies, 2025)
General Background Agricultural productivity depends on efficient and uniform planting methods. Specific Background Mechanical rice planting tools are developed to replace manual methods and improve consistency. Knowledge Gap However, limited studies focus on design selection based on systematic evaluation methods for rice planting machines. Aims This study aims to design and determine the best concept of a rice planting machine using the Ulrich and Eppinger method. Results The evaluation shows that Concept A achieves the highest score based on manufacturability, operation, maintenance, and cost criteria, and is capable of planting seedlings with a spacing of 25 cm × 25 cm. Novelty The study applies a structured concept selection approach combined with mechanical system design for rice planting. Implications The proposed design provides a practical solution to improve planting uniformity, reduce labor effort, and support agricultural efficiency. Keywords: Rice Planting Machine, Mechanical Design, Concept Selection, Agricultural Equipment, Planting Mechanism Key Findings Highlights Selected design achieved highest evaluation score Planting pattern maintained consistent grid spacing Integrated mechanism supports synchronized motion